Improving the VIII Grade Students’ Descriptive Text Writing Achievement by Using Roundtable Technique At Smpn 1 Sumberasih-Probolinggo - Ainun Amilatun Nazilah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This research was focusing on improving the VIII grade students’ descriptive text writing achievement by using roundtable technique at SMPN 1 Sumberasih, Probolinggo. This class room action research was selected by the researcher because based on the result of the interview with the English teacher; it was known that the students faced difficulties in writing a descriptive text especially in developing the ideas, choosing appropriate words, using correct tenses, and using correct mechanics. Therefore, the researcher tried to use Roundatble technique to solve those problems because Roundtable technique is kind of cooperative learning that allows the students to take turn in generating ideas related to the topic of writing. It is useful for brainstorming, reviewing, and practicing a skill.
reupload file repositori 31 maret 2026_kurnadi/keysa
Keywords: research; descriptive text